Analisis Faktor yang Memengaruhi Kinerja Kawasan Ekonomi Khusus (KEK) dan Peran Anggaran dalam Mendukung Pengembangan KEK - Tata Suharta; Muhammad Ramdhani Inayattulloh (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2024)
Economic development efforts in Indonesia face several central problems. One is the lack of investment. Developing Special Economic Zones (SEZs) is an alternative to overcoming investment challenges. The majority of optimal SEZs record cumulative investment realizations above IDR 10.0 trillion up to 2022 and provide an investment contribution of more than 5% in each region where the KEKs in question operate. However, of the 20 SEZs operating from 2012 to 2023, only seven are optimal. This research investigates the challenges in SEZ development employing a descriptive qualitative approach. This research was conducted through documentation studies, field observations, and focus group discussions using three SEZs as research objects, one in the optimal category and two in the not. This research identifies and compares several SEZ operational factors and finds funding flexibility, the capacity of area managers, the availability of infrastructure outside the area, and the availability of facilities and infrastructure within the area are factors that differentiate optimal and non-optimal SEZs. This study also highlights the budgeting condition for coordinating KEK development based on the concept of performance-based budgeting. The findings from this research are expected to provide insight into the development of KEK which is more focused towards optimal performance.